PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DALAM MASYARAKAT MULTIKULTURAL - Fina Surya Anggarini (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2019)
Islamic religious education in society is very important. Through education and teaching have an impact on good morals. Religious teachings are not merely rituals but come to the actualization of religious teachings and values in daily life. This writing aims to find out and discuss the development of Islamic religious education in society. This writing method is a literature review with a descriptive and exploratory approach. It can be concluded that the development/inculcation of Islamic religious education values in the community in an effort to improve the quality of faith includes (1) religious/faith education; to produce future young people who are strong in faith and piety and avoid misleading actions, such as drug abuse, brawl and promiscuity, (2) religious education; to teach children to build young people who are committed and accustomed to worship such as prayer, fasting, reading the Qur'an. (3) morality education-Karima; to give birth to a generation of rabbani, or a generation of pious and noble people.